Analysis of the Relationship between Religion and Culture through the “Nyumpet” Tradition in Jepara: Islamic Perspective and Local Wisdom - Roisah Fathiyatur Rohmah (JIA (Jurnal Ilmu Agama), 2024)
The relationship between religion and culture is an interesting thing to analysis, especially in Java which has various local cultures which are famous for their Javanese. Local culture that originates from generations of ancestors still exists today. Like the Nyumpet tradition in Jepara which is carried out by the owner of the party before holding a celebration, whether a wedding or circumcision event. The survival of ancestral traditions to this day also involves the role of religion in them, and vice versa. Religion can enter Javanese society and also involves existing traditions. The aim of this research is to review the relationship between religion and culture through the Nyumpet tradition in Jepara, considering that Nyumpet activity is a tradition that combines the role of religion and rituals inherited from ancestors. This research is qualitative research with data collection techniques through involved observation. This means that the researcher directly witnessed and took part in the Nyumpet tradition, because the researcher is part of the Jepara community. The results of this research show that religion and culture have a close relationship between the two. The existence of the Nyumpet ritual in Jepara society aims to prevent bad things from happening at celebration events. Nyumpet with various Ugo Rampe combined with Selametan shows that religion and culture are very strong in Jepara society and can have a psychological effect on the soul. The geographical location of Jepara district and the community's professions are also the reasons why Nyumpet in Jepara still exists today.